Awareness of Medical Negligence among Practitioners (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction The cases of medical negligence in the recent years have been gradually increasing. Unlessknowledge about medical negligence is strictly implicated in the medical practice the rate of medicalnegligence will increase. Nearly 50lakh Indians die due to medical negligence every year.Ain & Objective The present study was aimed to assess the level knowledge and awareness regardingmedical negligence among medical practitioners .Materials & Method The present cross sectional study was conducted in saveetha medical college andhospitals , Chennai. A total of 100 practitioners were studied . The study period was from 24th February to12th march 2019.Result ; In total , 100 medical practitioners were studied, of which almost all had knowledge about medicolegal cases , only 88 of them take precautions during handling medico legal cases . only 47% were aware ofthe punishments given for medical negligence.Conclusion The awareness among the practitioners is satisfactory. But 37% of the practitioners couldn’tdifferentiate medical negligence from medical errors. The knowledge about the punishments given for anact of medical negligence is not satisfactory only ,40% had knowledge inn that area. The attitude of takingprecautions during handling a medical legal case was satisfactory, only 12% of them don’t take precautions .